Gap dynamics in the U.S. between urban areas in the current trend and in sustainable scenario - Haoyu Wang; Xiuyuan Zhang; Shihong Du; Yuyu Zhou; Donghai Wu; Qian Wang; Lubin Bai; Bo Liu; Shuping Xiong (Geography and Sustainability)
The gap between the projected urban areas in the current trend (UAC) and those in the sustainable scenario (UAS) is a critical factor in understanding whether cities can fulfill the requirements of sustainable development. However, there is a paucity of knowledge on this cutting-edge topic. Given the extensive and rapid urbanization in the United States (U.S.) over the past two centuries, accurately measuring this gap between UAS and UAC is of critical importance for advancing future sustainable urban development, as well as having significant global implications. This study finds that although the 740 U.S. cities have a large UAC in 2100, these cities will encompass a significant gap from UAC to UAS (approximately 165,000 km²), accounting for 30 % UAC at that time. The study also reveals the spatio-temporal heterogeneity of the gap. The gap initially increases before reaching a inflection point in 2090, and it disparates greatly from −100 % to 240 % at city level. While cities in the Northwestern U.S. maintain UAC that exceeds UAS from 2020 to 2100, cities in other regions shift from UAC that exceeds UAS to UAC that falls short of UAS. Filling the gap without additional urban growth planning could lead to a reduction of crop production ranging from 0.3 % to 3 % and a 0.68 % loss of biomass. Hence, dynamic and forward-looking urban planning is essential for addressing the challenges of sustainable development posed by urbanization, both within the U.S. and globally.